How does the market value corporate sustainability performance? - Lourenço, I.; Branco, M.; Curto, J.; Eugénio, T. (Journal of Business Ethics, 2012)
This study provides empirical evidence on how corporate sustainability performance (CSP), as proxied by membership of the Dow Jones sustainability index, is reflected in the market value of equity. Using a theoretical framework combining institutional perspectives, stakeholder theory, and resource-based perspectives, we develop a set of hypotheses that relate the market value of equity to CSP. For a sample of North American firms, our preliminary results show that CSP has significant explanatory power for stock prices over the traditional summary accounting measures such as earnings and book value of equity. However, further analyses suggest that we should not focus on corporate sustainability itself. Our findings suggest that what investors really do is to penalize large profitable firms with low level of CSP. Firms with incentives to develop a high level of CSP not engaging on such strategy are, thus, penalized by the market.